The Effect Of Perceived Ease Of Use And Service Quality On Customer Loyalty Through Repurchase Intention As Intervening Variables (Case Study: Gofood Customers In Yogyakarta City) - Fauzi, Muhamad Ardan; Udayana, Ida Bagus Nyoman; Hutami, Lusia Tria Hatmanti (Perkumpulan Dosen Muda (PDM) Bengkulu, 2022)
This research examine the effect of perceived ease of use and service quality on customer loyalty and test whether repurchase intention acts as an intervening variable for the effect of perceived ease of use and service quality on Gofood customer loyalty in Yogyakarta City. This research is quantitative by taking 120 samples from Gofood customers in Yogyakarta City. The sampling method is non-probability and the sampling technique uses purposive sampling. Data was collected by sending a questionnaire link that was sent online to respondents. The data were analyzed using the IBM SPSS application. The results of this study indicate that the variable perceived ease of use (X1) has a positive and significant effect on repurchase intention (Z) with a value of 0.000. Then the service quality variable (X2) has a positive and significant effect on repurchase intention (Z) with a value of 0.000. The repurchase intention variable (Z) has a positive and significant effect on customer loyalty (Y) with a value of 0.000. Furthermore, the variable perceived ease of use (X1) has a positive and significant effect on customer loyalty (Y) with a value of 0.008. And the service quality variable (X2) has a positive and significant effect on customer loyalty (Y) with a value of 0.000. In addition, the results of the study also show that repurchase intention is able to act as an intervening variable for the influence of perceived ease of use and service quality on Gofood customer loyalty in the city of Yogyakarta.